Peroxiredoxin 6 mediates Gαi protein-coupled receptor inactivation by cJun kinase - Schattauer, SS; Land, BB; Reichard, KL; Abraham, AD; Burgeno, LM; Kuhar, JR; Phillips, PEM; Ong, SE; Chavkin, C (Nature Publishing Group, 2017)
Inactivation of opioid receptors limits the therapeutic efficacy of morphine-like analgesics and mediates the long duration of kappa opioid antidepressants by an uncharacterized, arrestin-independent mechanism. Here we use an iterative, discovery-based proteomic approach to show that following opioid administration, peroxiredoxin 6 (PRDX6) is recruited to the opioid receptor complex by c-Jun N-terminal kinase (JNK) phosphorylation. PRDX6 activation generates reactive oxygen species via NADPH oxidase, reducing the palmitoylation of receptor-associated Gαi in a JNK-dependent manner. Selective inhibition of PRDX6 blocks Gαi depalmitoylation, prevents the enhanced receptor G-protein association and blocks acute analgesic tolerance to morphine and kappa opioid receptor inactivation in vivo. Opioid stimulation of JNK also inactivates dopamine D2 receptors in a PRDX6-dependent manner. We show that the loss of this lipid modification distorts the receptor G-protein association, thereby preventing agonist-induced guanine nucleotide exchange. These findings establish JNK-dependent PRDX6 recruitment and oxidation-induced Gαi depalmitoylation as an additional mechanism of Gαi-G-protein-coupled receptor inactivation.Opioid receptors are important modulators of nociceptive pain. Here the authors show that opioid receptor activation recruits peroxiredoxin 6 (PRDX6) to the receptor-Gαi complex by c-Jun N-terminal kinase, resulting in Gαi depalmitoylation and enhanced receptor-Gαi association.